A case of spastic quadriparesis secondary to enteric fever. (July 2021) - Bhatta, Ajay; Kumar, Prabhat
Enteric fever is a systemic disease characterised predominantly by fever and abdominal pain, caused by dissemination of Salmonella Typhi or Salmonella Paratyphi . Enteric fever can affect many organ systems including liver, gastrointestinal tract, kidney and brain. Neurological manifestations occur in 2%–40% of patients and include meningitis, Gullian-Barré syndrome, neuritis and neuro-psychiatric symptoms. Spastic quadriparesis is a rare complication.